Finding the key to successful L2 learning in groups and individuals - Lowie, Wander; van Dijk, Marijn; Chan, Huiping; Verspoor, Marjolijn (Studies in Second Language Learning and Teaching, 2017)
A large body studies into individual differences in second language learning has shown that success in second language learning is strongly affected by a set of relevant learner characteristics ranging from the age of onset to motivation, aptitude, and personality. Most studies have concentrated on a limited number of learner characteristics and have argued for the relative importance of some of these factors. Clearly, some learners are more successful than others, and it is tempting to try to find the factor or combination of factors that can crack the code to success. However, isolating one or several global individual characteristics can only give a partial explanation of success in second language learning. The limitation of this approach is that it only reflects on rather general personality characteristics of learners at one point in time, while both language development and the factors affecting it are instances of complex dynamic processes that develop over time. Factors that have been labelled as “individual differences” as well as the development of proficiency are characterized by nonlinear relationships in the time domain, due to which the rate of success cannot be simply deduced from a combination of factors. Moreover, in complex dynamic systems theory (CDST) literature it has been argued that a generalization about the interaction of variables across individuals is not warranted when we acknowledge that language development is essentially an individual process (Molenaar, 2015). In this paper, the viability of these generalizations is investigated by exploring the L2 development over time for two identical twins in Taiwan who can be expected to be highly similar in all respects, from their environment to their level of English proficiency, to their exposure to English, and to their individual differences. In spite of the striking similarities between these learners, the development of their L2 English over time was very different. Developmental patterns for spoken and written language even showed opposite tendencies. These observations underline the individual nature of the process of second language development.